Characterizing the Antimicrobial Function of a Dairy-Originated Probiotic, Propionibacterium freudenreichii, Against Multidrug-Resistant Salmonella enterica Serovar Heidelberg in Turkey Poults - Nair, Divek V. T.; Kollanoor Johny, Anup (Frontiers in Microbiology, 2018)
Antimicrobial potential of a dairy-origin probiotic bacteria, Propionibacterium freudenreichii, against multidrug-resistant (MDR) Salmonella Heidelberg (SH) in turkey poults was determined in the current study. Employing in vitro experiments, two strains (subsp.) of P. freudenreichii: P. freudenreichii freudenreichii B3523 (PF) and P. freudenreichii shermanii B4327 (PS) were tested for their ability to resist low pH (2.5) and bile salts (0.3%). In addition, the ability of the strains to adhere to and invade avian epithelial cells was determined after exposure to Propionibacterium strains followed by SH challenge. Moreover, the antibacterial activity of the strains’ cell-free culture supernatants (CFCSs) were tested against three major foodborne pathogens, including SH. Furthermore, the susceptibility of the strains to common antibiotics used for human therapy was determined. The hemolytic properties of the strains were determined in comparison to Streptococcus pyogenes, a known hemolysis-causing pathogen. Appropriate controls were kept in all studies. Using two in vivo experiments, PF was tested against SH colonization of poult ceca and dissemination to liver and spleen. The 4 treatment groups were: negative control, PF control (PFC), SH control (SC) and a test group (PFS; PF+SH). The poults in the PFC and PFS groups were inoculated with 1010 CFU ml-1 PF from day 1 through crop gavage and subsequently supplemented through drinking water. On day 7, SC and PFS groups were challenged with SH at 106 CFU ml-1, and after 7 days, cecum, liver, and spleen were collected for determining surviving SH populations. Results indicated that both PF and PS resisted pH=2.5 and 0.3% bile salts with surviving populations comparable to the control and adhered well onto the avian epithelial cell lines. The strains were susceptible to antibiotics and did not invade the epithelial cells or exhibit hemolytic properties. The CFCSs were highly bactericidal against all tested pathogens. In turkey poults, PF significantly reduced cecal colonization of SH and the dissemination of the pathogen to the liver, compared to the SH challenge controls (P<0.05). Results reveal that PF, a non-host GIT-derived probiotic, could be an antibiotic alternative to prevent the early colonization of SH in poults, improving the preharvest safety of turkeys.